The Study of Needs and Factors Explaining for Participatory to Create Well-Being Based on New Normal Life of the Older Adult among Urban Community, Ratchaburi Province. - Thanaboonpuang, Parinyaporn; Intana, Jiriya; Khamthana, Phenchamart (NU Journal of Nursing and Health Sciences, 2023)
This mixed method research was to study the needs assessment, the level of participation and factors explaining for participatory to create well-being based on new normal life for older adult among urban community, Ratchaburi province.The sample of quantitative data were 421 older adults and qualitative data were 35 person.The research instrument consisted of need assessment questionnaire, semi-structured interview and focus group form that content validity between 0.66 - 1.00 and reliability of subscales for questionnaire were 0.83 and 0.87 respectively. The data were then analyzed using descriptive statistics such as percentage, mean, standard deviation, the priority needs index analysis and content analysis. The results revealed that needs must urgently develop the participation in religious activities/festivals (PNIModified= 0.59) and the receiving welfare and benefits (PNIModified = 0.56). The factors explaining for participatory to create well-being based on new normal life were community leadership, health literacy, social support and building collaboration network. Therefore, the approaches to promote participation in creating well-being based on new normal life for older adult that should be consider needs and focus on promote community leadership, health literacy, social support and building collaboration network. In order to community strengthen and be able to take care of the older adult according to the well-being guidelines based on new normal life sustainably.